A reverse translational study of PPAR-α agonist efficacy in human and rodent models relevant to alcohol use disorder - Barbara J. Mason; David Estey; Amanda Roberts; Giordano de Guglielmo; Olivier George; John Light; Mike Stoolmiller; Susan Quello; Michael Skinner; Farhad Shadan; Adnan Begovic; Mark C. Kyle; et al. (Neurobiology of Stress, 2024)
Alcohol Use Disorder (AUD) is a chronic relapsing disorder affecting an estimated 283 million individuals worldwide, with substantial health and economic consequences. Peroxisome proliferator-activated receptors (PPARs), particularly PPAR-α and PPAR-γ, have shown promise in preclinical studies as potential therapeutic targets for AUD. In this human laboratory study, we aimed to translate preclinical findings on the PPAR-α agonist fenofibrate to a human population with current AUD. We hypothesized that, relative to placebo, fenofibrate at the highest FDA-approved dose of 145 mg/d would attenuate responsiveness to in vivo alcohol cues in the lab and reduce drinking under natural conditions. However, the results did not show significant differences in craving and alcohol consumption between the fenofibrate and placebo groups. Reverse translational studies in rodent models confirmed the lack of fenofibrate effect at human-equivalent doses. These findings suggest that inadequate translation of drug dose from rodents to humans may account for the lack of fenofibrate effects on alcohol craving and consumption in humans with AUD. The results highlight the need for new brain-penetrant PPAR-α agonists to adequately test the therapeutic potential of PPAR-α agonists for AUD, and the importance of reverse translational approaches and selection of human-equivalent doses in drug development.